State of the art in catalytic oxidation of chlorinated volatile organic compounds - Aranzabal, Asier; Pereda-Ayo, Beñat; González-Marcos, M. Pilar; González-Marcos, José A.; López-Fonseca, Rubén; González-Velasco, Juan R. (Chemical papers, 2014)
Chlorine-containing organic compounds (Cl-VOC) require special attention due to their distinct toxicity, high stability and persistence in the environment. Removal of Cl-VOC by catalytic oxidation over a wide variety of catalysts has been presented in literature. This paper reviews the state of the art in this subject, including different model compounds, nature of catalysts, and oxidation activity. Catalyst selectivity (CO 2 vs. CO and HCl vs. Cl 2 ), by-products formation and the causes of deactivation are also analyzed as the most important factors in the catalyst selection for practical applications.